Development of customer retention activities in the automotive industry : the case of Nissan Nordic Europe Oy - Andreoni, Pietro (My University, 2011)
Purpose: The purpose of this thesis is the enhancement of the knowledge in the research of the customer loyalty activities from the automotive industry perspective. The Automotive industry is characterized from different purchase cycles comparing to a traditional retail business, as the contact between customer and supplier are very limited across the years and with very large amount of value. Therefore the carmakers have to plan carefully their loyalty activities in order to retain their customers after that the first purchase have been done long time before. The purpose of this thesis is to compare how the current theoretical understanding of design, execution and evaluation of loyalty activities it applies to a real study case and by doing so finding what the company analyzed is currently lacking and what should implement in order to improve its customer retention activities. Design/methodology/approach: A framework where the interview is based from, is developed from the theoretical part. The framework contains the main key-points that wants to be discussed in the interview and then analyzed. A company (Nissan Nordic Europe Oy - NNE) from the automotive industry is selected after knowing that is at the moment implementing its loyalty activities. The approach to the empirical case is to compare the outcome from the interview with the theory and notice the possible lacking of the company. Findings: NNE has just recently started its loyalty activities. From the design perspective, a more qualitative data collection about the customers would be better in order to design different activities for different clusters of customers. From the execution and implementation, the setting of the company allows the manager in charge to work with no blockings. From the evaluation of the activities, a direct feedback system from the customers would avoid misunderstandings whether if the activity is successful because deployed by Nissan or by the dealership. Also a definition of precise targets to achieve for each activity would facilitate the evaluation. Research limitations/future developments: The paper analyzes the design of customer loyalty activities from the one company point of view. Further research could be done from the customer perspective (its customer loyalty experience) or from dealership perspective. Also comparing this case with another case would make possible an analysis cross-empirical and not only against the theory. Originality/value: This paper is contributing to extending the knowledge about customer loyalty research and in specific describing the design of loyalty activities of one of the major car manufacturer in the world.
Keywords: KEYWORDS: “Loyalty activities”; “automotive industry”; “relationship marketing”; “retention activities”.; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|